Evaluasi Proses Program Pendidikan Keaksaraan Dasar Perspektif Discrepancy Evaluation Model - Marliza Oktapiani (Alignment:Journal of Administration and Educational Management, 2020)
The purpose of this study is to find out how to evaluate the process of literacy education programs from the perspective of the discrepancy evaluation model. The method used in this research is qualitative method. The results of this study indicate that there are gaps in the aspects of the program process which have three gaps including the preparation of learning tools (syllabus and lesson plans), improvement of reading culture, assessment of learning processes and assessment of final results. The achievements and impacts of the basic literacy education program have not been maximal in meeting basic literacy education program standards. In conclusion, the program analyzed its gaps and provided problem solving in every aspect based on the stage of the discrepancy evaluation model. Keywords: Process Evaluation, Basic Literacy, Discrepancy Evaluation Model